2019
DOI: 10.1515/bmc-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

The disordered boundary of the cell: emerging properties of membrane-bound intrinsically disordered proteins

Abstract: We define the disordered boundary of the cell (DBC) as the system formed by membrane tethered intrinsically disordered protein regions, dynamically coupled to the underlying membrane.The emerging properties of the DBC makes it a global system of study, which cannot be understood from the individual properties of their components. Similarly, the properties of lipid bilayers cannot be understood from just the sum of the properties of individual lipid molecules.The highly anisotropic confined environment, restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…This suggests that protein function may be related to the overall level of disorder and could be used to refine variant interpretation in IRDs. Previous studies have demonstrated that IDRs are more abundant in membrane proteins than in the complete proteome, with more than 50% of transmembrane proteins containing IDRs composed of at least 30 residues [ 15 , 16 ]. Our results show that Group 2 transmembrane proteins exhibit the second-highest degree of disorder, confirming this finding.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that protein function may be related to the overall level of disorder and could be used to refine variant interpretation in IRDs. Previous studies have demonstrated that IDRs are more abundant in membrane proteins than in the complete proteome, with more than 50% of transmembrane proteins containing IDRs composed of at least 30 residues [ 15 , 16 ]. Our results show that Group 2 transmembrane proteins exhibit the second-highest degree of disorder, confirming this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Today it is well accepted that membrane deformations and associated protein functions are coupled mechanisms (Haylock et al, 2020;Song et al, 2019), with complex emergent properties derived in part from the highly heterogeneous nature of the bilayers (Nicolson, 2014;Mohammad et al, 2019), or as suggested by Lamparter and Galic (2020), a versatile, adaptive composite material. Membrane proteins may dynamically modify their curvature preference upon external stimuli (Stroh and Risselada, 2021), also making the coupled mechanism dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…The strong electrostatic field in the vicinity of the membrane (10 5 Vcm −1 ) [11] can substantially change the conformational landscape, triggering additional interactions, especially in intrinsically disordered proteins with multiple charged residues [2].…”
Section: Asymmetric Distribution Of Charged Lipids In Membranesmentioning
confidence: 99%
“…The strong electrostatic field in the vicinity of the membrane (10 5 Vcm −1 ) [11] can substantially change the conformational landscape, triggering additional interactions, especially in intrinsically disordered proteins with multiple charged residues [2]. Interestingly, various toxins interacting with the outer leaflet, enriched in phosphatidylcholine headgroups, have tyrosine residues participating in cation-p interactions with the positively charged choline headgroup [15,16].…”
Section: Asymmetric Distribution Of Charged Lipids In Membranesmentioning
confidence: 99%
See 1 more Smart Citation